Improved Noise Immunity for Two-Sample PLL Applicable to Single-Phase PFCs - Lamo-Anuarbe, Paula; Azcondo, Francisco J.; Pigazo, Alberto (2021 IEEE 22nd Workshop on Control and Modelling of Power Electronics, COMPEL 2021, 2022)
Synchronization in a single-phase Power Factor Correction (PFC) is deteriorated, among others, by the combination of the noise introduced by the grid voltage sensing, conducted EMI, the ADC resolution and the sampling frequency used. Low signal-to-noise ratios (SNR) reduce the performance of the Two-Sample (2S) Phase Locked Loop (PLL). This effect can be compensated by including a smoothing filter action without increasing the overall complexity significantly. The resulting 2S with smoothing (2SS) is evaluated and validated by simulation and experimentally over a Totem Pole PFC.
Keywords: noise immunity; PLL; synchronization; Scopus(2); WOS(2)